Discussion on seven best practices of successful organizations & Biman Bangladesh Airlines Limited - Hashmat, Fahad Ibne (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2014.